The Effectiveness of the Development of Nursing Standard of Severe Substance Use Disorder - Klingularb P, Chotsaengthong W, Numto A, Makan S (Journal of The Department of Medical Services, 2020)
Background: A nursing standard was an important tool of nursing services quality insurance. This study was a research and development Objective: The aiming to study and develop a nursing standard for drug addicts with a severe substance use disorder. The research was divided into three steps; (1) surveying and investigating the background of the problem, (2) developing the nursing standard for addicts with a severe substance use disorder by Mason’s concept (3) assessing the result of the guideline. Method: The research sample comprised of three groups. The first sample group was 20 nurse administrators and registered nurses (head ward). The second group of the sample was researcher team, and the third group consisted of 12 registered nurses and 20 severe substance use disorder. The research instruments comprised of a semi - structured interview question, a feedback questionnaire for the nursing standard, a satisfied questionnaire for the nurses, a knowledge understanding and skills of taking care themselves measurement form, the analysis methods were a content analysis, a descriptive statistic and Wilcoxon matched–pairs signed-rank. Result: The result indicated that; (1) seven nursing standard for drug addicts with a severe substance use disorder has been launched, the effectiveness of nursing standard indicated that (2) The satisfaction of the nurses on the guideline was very good level and (3) The score of the post-test of knowledge understanding and skills of taking care themselves was significantly higher than pretest at .05. Conclusion: The result showed that the nursing standard was effective and practical.